(untitled) (Transactions of the Association of European Schools of Planning, 2019)
Information and Communication Technologies (ICT) enable individuals to travel more flexibly. The choice of location for social activities has become very flexible. In addition to this, land-use characteristics also play a vital role in the location of social activities. This work aims to analyse the influence of land-use characteristics, ICT use, and social networks in the destination choices for face-to-face social activities of university students during both weekdays and weekends. Students from the two different campuses of the Instituto Superior Técnico were presented with an online questionnaire, which was intended to collect information about their use of ICT and social networks, in addition to their travel characteristics and socio-demographics. Emphasis was made upon capturing the characteristics of social networks and ICT usage. Information on land-use characteristics was obtained from secondary sources. Factor analysis was initially carried out to extract factors related to the use of ICT and social networks; these were later used to model the destination choice for social activities. The alternatives considered for destination choice included: home or the vicinity thereof, university or the vicinity thereof, other locations (further away from home and university), and evenly spread locations – having no specific priority for any of the other three locations considered. The analysis was performed separately for travel during weekdays and weekends so that an understanding of the differences and similarities in behaviour during these different time periods could be garnered. A multinomial logit model was estimated to model this choice. The results point to the relevance of land-use characteristics, the location of close friends, and modes of interaction. Individuals residing in more accessible central, and denser areas, were more likely to have activities distributed evenly across the city. These results stress the relevance of accessibility in allowing larger and more diverse spaces to be used for social activities.